Digitalisation and Public Policy in Africa
XXVII, 381 p. 25 illus.
Keywords: This book examines the ways in which government-owned technologies (GovTechs) and technologies owned by civil society organisations (CivicTechs) can be integrated into policy processes to enhance interactions between citizens and governments, and ensure effective, efficient, and accountable public service delivery. It takes stock of current technological innovations, and assesses the ways in which they can be aligned with GovTechs and CivicTechs to improve African governments' capacities in public policy and governance processes. The first part of the book traces the emergence of digital technologies in public administration, and assesses their benefits and challenges, especially in the Global South. The following chapters present case studies from across Africa and various policy sectors to show how GovTechs and CivicTechs operate. They demonstrate how digital platforms can be used to protect data, enhance democracy, improve food systems, and reduce corruption. The book will appeal to all those interested in public policy, public administration, emerging technologies, and African politics. Gedion Onyango is Research Fellow at the Firoz Lalji Institute for Africa, London School of Economics and Political Science, UK. Geci Karuri-Sebina is Associate Professor at the School of Governance, University of Witwatersrand, South Africa.